Support needs, received support and mental well-being in Austrian farmers: a mixed-methods approach - Humer, Elke; Gächter, Afsaneh; Pieh, Christoph; Neubauer, Viktoria (Frontiers in Public Health, 2025)
IntroductionAlthough Austrian farmers are at increased risk for mental ill health, there is limited research on their specific support needs and hardly any evidence on the prevalence of these support requirements. This study aims to explore the mental health support needs of Austrian farmers and to identify the types of support they consider most useful.MethodsAn online survey was conducted among 2,006 Austrian farmers. Participants completed standardized questionnaires assessing mental health parameters—including the PHQ-9 (depression), GAD-7 (anxiety), ISI-2 (insomnia), PSS-4 (perceived stress), WHO-5 (well-being), and CAGE (alcohol abuse)—and answered a dichotomous question regarding their desire for mental health support. Those who indicated a wish for support were invited to provid free-text descriptions of the specific type of help they desired. Additionally, farmers were asked whether they were already receiving support to improve their mental well-being. A mixed-methods approach was used to analyze both the quantitative mental health data and the qualitative free-text responses.ResultsApproximately 32% of the farmers expressed a desire to receive support to improve their mental well-being. Qualitative analysis of the free-text responses revealed a variety of support wishes, with coaching, counselling, mediation, and psychotherapy being the most common. Other prominent themes were the need for practical support related to farm work, time for recreation, financial support, and enhanced communication. Furthermore, around 14% of participants reported already receiving some form of mental health support. Farmers who either desired or were receiving support exhibited higher levels of depression, anxiety, insomnia, alcohol abuse, and perceived stress compared to those without such support needs.ConclusionThe study identifies a vulnerable subgroup within the Austrian farming community that experiences significant mental health challenges and expresses clear support needs. These findings emphasize the importance of developing tailored interventions that address both the psychological and practical aspects of farmers’ well-being, thereby enhancing resilience and improving overall mental health outcomes in this essential occupational group.